Depresión y su relación con el consumo de sustancias psicoactivas, el estrés académico y la ideación suicida en estudiantes universitarios colombianos (2018)
Several investigations in Colombia have reported that the two psychoactive substances most consumed by young people aged 10 to 24 years are alcohol (legal) and marijuana (illegal). The aim of this study was to analyze the relationship between the consumption of these two substances and depression, academic stress and suicidal ideation in a sample of 477 Colombian university students aged 18 to 25 years. The type of research was quantitative, transversal, with a non-experimental design of correlational level. Depression correlated with alcohol consumption (ρ = 0.131, p <0.01), with cannabis use (ρ =, 147, p <0.01), with academic stress (ρ = 0.531, p <0,01), but not with suicidal ideation. There were no correlations between substance use and academic stress, nor between consumption and suicidal ideation. The latter only correlated with academic stress (ρ = 0.112, p <0.05). The results could support the hypothesis of depression as a mediator between substance use and academic stress and suicidal ideation. The importance of elucidating the correlation (establishing causality) between substance use and depression, and between depression and academic stress is analyzed and highlighted.Keywords: psychoactive substances, depression, academic stress, suicidal ideation, university students